SLAMF7 and SLAMF8 receptors shape human plasmacytoid dendritic cell responses to intracellular bacteria - Pellegrini, Joaquín Miguel; Keriel, Anne; Gorvel, Laurent; Hanniffy, Sean; Arce-Gorvel, Vilma; Bosilkovski, Mile; Solera, Javier; Méresse, Stéphane; Mémet, Sylvie; Gorvel, Jean-Pierre (AMERICAN SOCIETY FOR CLINICAL INVESTIGATION INC, 2025)
Plasmacytoid dendritic cells (pDCs), professional type I IFN-producing cells, have been implicated in host responses against bacterial infections. However, their role in host defense is debated, and the operating molecular mechanisms are unknown. Certain signaling lymphocyte activation molecule family (SLAMF) members act as microbial sensors and modulate immune functions in response to infection. Here, human blood transcriptomic analyses reveal the involvement of SLAMF7 and SLAMF8 in many infectious diseases, with elevated levels associated with type I IFN responses in salmonellosis and brucellosis patients. We further identify SLAMF7 and SLAMF8 as key regulators of human pDC function. They activate pDC maturation and cytokine production during infection with bacteria that induce acute (Salmonella) or chronic (Brucella) inflammation. SLAMF7 and SLAMF8 signal through NF-κB, IRF7, and STAT-1, and limit mitochondrial ROS accumulation upon Salmonella infection. Remarkably, this SLAMF7/8-dependent control of mitochondrial ROS levels favors bacterial persistence and NF-κB activation. Overall, our results unravel essential shared multifaceted roles of SLAMF7 and SLAMF8 in finely tuning human pDC responses to intracellular bacterial infections with potential for future diagnostic and therapeutic applications.